Finding alternative community-based learning delivery for parenting skills during COVID-19 for mothers with children aged 0–3 Years - Pandia, Weny Savitry S.; Suwartono, Christiany; Hestyanti, Yohana Ratrin; Tanuwijaya, Kartika Anggita; Abraham, Natasha Sheir; Henry, Eddy; Herarti, Fitriana; Irwanto (Frontiers in Education, 2024)
Parenting training has been considered crucial in improving the effectiveness of child development. The Tanoto Foundation's parenting program intervention was started in 2021 when the Covid 19 impacted government policies in Indonesia. Preventive measures by limiting mobility undermine the sustainability of the parenting intervention organized in face-to-face fashion. The study aimed to find alternative modes of intervention among Face-to-face, Blended, Online with facilitators, and Self-Learning for parenting skills learning delivery during an emergency. This study carried out a oneyear non randomized quasi field experiment with a mixed quantitative-qualitative method. SIGAP Q, The HOME Inventory, and CREDI were used as quantitative measurement; while interviews and Focused Group Discussions (FGDs) as qualitative tools for data collection. Analysis of the quantitative data was conducted using Multiways ANOVA and qualitative data analysis using thematic analysis. The study found that all intervention modalities delivered positive outcomes, where Face to Face delivered the largest gain, followed by Online with Facilitators, Blended, and Online Self-Learning (web-based learning management system). As an alternative, Online with Facilitators is the best in delivering parenting materials followed by Online Self-Learning (independent) modes of intervention. Blended and Online based provide alternative models in emergency contexts. Implications are discussed in this article.